Heat transfer of intake port for hydrogen fueled port injection engine: A steady state approach - M. M., Rahman; Hamada, Khalaf I.; K., Kadirgama (Academic Journals, 2011)
The steady state heat transfer analysis of intake port for hydrogen fueled port injection engine is investigated. One dimensional gas dynamics was described by the flow and heat transfer in the components of the engine model. The engine model is simulated with variable engine speed and equivalence ratio (φ). Engine speed varied from 2000 to 5000 rpm with increment of 1000 rpm, while equivalence ratio changed from stoichiometric to lean limit. The effects of equivalence ratio and engine speed on heat transfer characteristics for the intake port are presented in this paper. The baseline engine model is verified with existing previous published results. Comparison between hydrogen and methane fuel was made. The obtained results show that the engine speed has the same effect on the heat transfer coefficient for hydrogen and methane fuel, while equivalence ratio has effect on heat transfer coefficient in case of hydrogen fuel only. Rate of increase in heat transfer coefficient comparison with stoichiometric case for hydrogen fuel are: 4% for (φ = 0.6) and 8% for (φ = 0.2). While negligible effect was found in case of methane fuel with change of equivalence ratio. But methane is given greater values about 11% for all engine speed values compare with hydrogen fuel under stoichiometric condition. The blockage phenomenon affected the heat transfer process dominantly in case of hydrogen fuel; however, the forced convection was influencing the heat transfer process for hydrogen and methane cases.